Estimations of Occupational and Regional Matching Efficiencies Using Stochastic Production Frontier Models - René Fahr; Uwe Sunde (Institute for the Study of Labor (IZA), 2002)
By applying a stochastic production frontier approach to the matching process of unemployed and vacancies, this paper provides novel detailed insights into the process of job creation. For different labor markets as defined by occupation and region, the methodology produces estimates of the relative importance of demand and supply factors for the creation of new jobs, and of the overall efficiency of job creation. Some crucial determinants of the overall matching efficiency are identified and analyzed. This allows to make differentiated statements about the appropriateness of labor market policies, and therefore provides policy makers with novel relevant information.
Keywords: C24; J64; 330; matching efficiency; stochastic frontier; occupational unemployment; regional unemployment; Arbeitsmarkt; Matching; Technische Effizienz; Stochastischer Prozeß; Schätzung; Deutschland